2006
DOI: 10.5194/adgeo-6-155-2006
|View full text |Cite
|
Sign up to set email alerts
|

Sea level height, sea surface temperature, and tuna yields in the Panama bight during El Niño

Abstract: Abstract. Between 1988 and 1998, annual tuna landings at Buenaventura (Colombian Pacific) are correlated with the sea surface temperature in the central Equatorial Pacific (r=0.78, p<0.05) and the sea level height at Buenaventura (r=0.76, p<0.05) and Balboa (Panama) (r=0.79, p<0.05). Seasonal oceanic upwelling is forced by the Panama wind jet, which may favour oceanic fisheries such as tuna. Here we first apply a bivariate correlation method (Pyper and Peterman, 1994) and then a multivariate approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
1
6
0
1
Order By: Relevance
“…The distribution of tuna in the Indian Ocean and its relation to oceanic structure has been widely discussed (Chen et al 2005 ; Song et al 2009 ). Our results provide confirmation that the temporal fluctuations of the catches of tuna species in the Indian Ocean during El Nino years, as reported earlier in the Panama bight (United States) Pacific coast (Pedraza and Dıaz-Ochoa 2006 ), and in the western Pacific (Lehodey et al 2008 ). ENSO events seem to be the primary source of variability of tuna landings in the Indian Ocean during 1980–2010.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The distribution of tuna in the Indian Ocean and its relation to oceanic structure has been widely discussed (Chen et al 2005 ; Song et al 2009 ). Our results provide confirmation that the temporal fluctuations of the catches of tuna species in the Indian Ocean during El Nino years, as reported earlier in the Panama bight (United States) Pacific coast (Pedraza and Dıaz-Ochoa 2006 ), and in the western Pacific (Lehodey et al 2008 ). ENSO events seem to be the primary source of variability of tuna landings in the Indian Ocean during 1980–2010.…”
Section: Resultssupporting
confidence: 92%
“…Recent studies have found that tuna population dynamics is influenced by the ENSO phenomenon (Lehodey et al 2008 ). Interestingly, few investigations have been conducted on the relationship between fluctuations in oceanic environmental conditions and tuna catch in the Pacific regions and the Panama bight during El Nino years (Lehodey et al 1997 ; 2003 ; Pedraza and Dıaz-Ochoa 2006 ). Studies have indicated that Pacific Ocean tunas have thermal limits for maximum abundance of Yellowfin between 20° to 30°C and Skipjack between 20° to 29°C (Stretta 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct oceanographic signatures in turn signify enhanced trophic interactions, physiological and foraging advantages, and thus provide high ecological and economic importance. Large pelagic fish as well as commercial fishing vessels recognize that prey organisms aggregate at ocean hotspots, which are mostly represented by ocean fronts, eddies and upwelling zones [ 2 , 3 , 4 ]. Thermal fronts are important congregating spots for many valuable pelagic species in Baja California-Bering Sea [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lebih lanjut Beverly et al (2003) menjelaskan bahwa penentuan daerah penangkapan ikan rawai tuna dipengaruhi oleh beberapa faktor seperti suhu permukaan air laut, pertemuan arus, gerakan spiral air laut (eddies) dan pergerakan air laut dingin (upwelling). Suhu permukaan laut dan pergerakan air laut (upwelling) terbukti mempengaruhi distribusi dan hasil tangkapan ikan pelagis besar seperti kelompok tuna dan ikan berparuh (Kumar et al, 2014;Boyce, 2006;Pedraza & Diaz-Ochoa, 2006).…”
Section: Bahasanunclassified